Consensus guidelines for the management of brain stem and diffuse midline glioma for low- and middle-income countries - Hafiza Fatima Aziz; Naureen Mushtaq; Fatima Suleman; Asim Hafiz; Mohammad Hamza Bajwa; Ahmed Gilani; Kaynat Siddiqui; Altaf Ali Laghari; Muhammad Usman Khalid; Saqib Kamran Bakhshi; Syed Ather Enam; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement) (Journal of the Pakistan Medical Association, 2024)
The understanding of brainstem gliomas and diffuse midline gliomas has significantly increased in the last decade. However, the management paradigm remains a dilemma. The critical location is the foremost factor dictating the outcome. Recent advancements in the field of neuro-oncology are pushing the boundaries of optimal care in the developed world nevertheless, the strategies in low- and middle-income countries (LMICs) need to be tailored according to the resources to improve outcome. The objective of these guidelines is to provide an algorithm-based management plan to cater challenges for healthcare providers in LMICs. Keywords: Algorithms, brain stem, glioma.